Taxonomy and ecology of Fragilaria billingsii sp. nov. and analysis of type material of Synedra rumpens var. fusa (Fragilariaceae, Bacillariophyta) from Brazil - Wengrat, Simone; Morales, Eduardo A.; Wetzel, Carlos E.; Almeida, Pryscilla D.; Ector, Luc; Bicudo, Denise C. (Phytotaxa, 2016)
Synedra rumpens var. fusa was originally described by Patrick, but there are only a few subsequent records of this variety in the literature. Analysis of samples from Brazilian reservoirs containing a morphologically similar taxon led us to the analysis of the type material of S. rumpens var. fusa, performed using light (LM) and scanning electron microscopy (SEM). In the present manuscript, an amendment to the description of the var. fusa is made and its transfer to the genus Fragilaria as F. fusa comb. et stat. nov. is proposed. Moreover, Fragilaria billingsii sp. nov. is described from a large multipurpose reservoir from the State of São Paulo, Brazil. Comparative discussions with morphologically related taxa found in the literature are presented. Regarding ecological preferences, the new species was found living in slightly acidic and meso-eutrophic waters.